A rare case of an open transverse patella fracture in a 5-year-old child. (October 2022) - Nguyen, Antony; Vather, Mehr; Haj Younes, Bachar; Jones, Hugh; Molnar, Robert; Dave, Jayker
Abstract: Patella fractures in children are rare accounting for 1 % of all paediatric fractures. Rarer still are transverse patella fractures in children with only 1 case previously described in the literature of a child less than the age of 6. We present the second case in the literature of a transverse patella fracture in a child, and the only case of a transverse fracture in a partially ossified patella in a 5-year-old. Our patient suffered an open patella fracture following fall with a flexed knee onto a broken tile. The case was successfully managed with adult fixation principles of patella fractures with a tension band wire construct. The patient had regular follow-up with knee radiographs showing a well healed fracture and a good range of motion of the knee at 3 months. The hardware was subsequently removed with no complications. In conclusion, we present an extremely rare case of an open transverse patella fracture in a child, utilising adult fixation principles of a patella which resulted in a successful outcome for the patient.